Respiratory support in COVID-19 patients, with a focus on resource-limited settings - Dondorp, AM; Hayat, M; Aryal, D; Beane, A; Schultz, MJ (American Society of Tropical Medicine and Hygiene, 2020)
The ongoing novel coronavirus disease (COVID-19) pandemic is threatening the global human population, including in countries with resource-limited health facilities. Severe bilateral pneumonia is the main feature of severe COVID-19, and adequate ventilatory support is crucial for patient survival. Although our knowledge of the disease is still rapidly increasing, this review summarizes current guidance on the best provision of ventilatory support, with a focus on resource-limited settings. Key messages include that supplemental oxygen is a first essential step for the treatment of severe COVID-19 patients with hypoxemia and should be a primary focus in resource-limited settings where capacity for invasive ventilation is limited. Oxygen delivery can be increased by using a non-rebreathing mask and prone positioning. The presence of only hypoxemia should in general not trigger intubation because hypoxemia is often remarkably well tolerated. Patients with fatigue and at risk for exhaustion, because of respiratory distress, will require invasive ventilation. In these patients, lung protective ventilation is essential. Severe pneumonia in COVID-19 differs in some important aspects from other causes of severe pneumonia or acute respiratory distress syndrome, and limiting the positive endexpiratory pressure level on the ventilator may be important. This ventilation strategy might reduce the currently very high case fatality rate of more than 50% in invasively ventilated COVID-19 patients.